Application value of serum high mobility group protein B1 (HMGB1) and soluble triggering receptor-1 (sTREM-1) levels in the prognostic assessment of trauma: HMGB1 and sTREM-1 levels in prognostic assessment of trauma - Tang, Lulu; Shan, Dan; Zhang, Heng; Lin, Shuli; Ji, Xubiao (Journal of Medical Biochemistry, 2025)
Objective: This study analyzed the clinical value of serum high mobility group protein B1 (HMGB1) and soluble triggering receptor 1 for myeloid cells (sTREM-1) in the prognostic assessment of trauma patients.Methods: In this prospective cohort study, 92 patients with multiple injuries admitted to our hospital from December 2022 to December 2024 were selected. The patients at admission were divided into three groups according to their injury severity score: the minor injury group (n=24), the severe injury group (n=58), and the severe injury group (n=10). The patients were divided into the MODS group (n=20) and the non-MODS group (n=72) on the basis of whether they had multiple organ dysfunction syndrome (MODS) after admission. The patients were divided into a death group (n=13) and a survival group (n=79) on the basis of their outcomes within 28 days after the occurrence of trauma. Venous blood was collected from an empty stomach at 24 hours, 72 hours and 7 days after injury. The levels of serum HMGB1 and sTREM-1 were detected via enzyme-linked immunosorbent assay (ELISA). Moreover, the injury severity score (ISS), Acute Physiology and Chronic Health Evaluation (APACHE II), complications during hospitalization (infection, MODS, etc.) and 28-day survival of the patients were recorded.Results: The concentrations of serum HMGB1 and sTREM-1 in the trauma group were significantly greater than those in the control group (P
Keywords: Multiple injuries; High mobility group protein B1; Soluble triggering receptor-1 of myeloid cells; Prognosis assessment